The use of technology to improve organizational performance through corporate entrepreneurship - Rodrigo Martín Rojas; Nuria González Álvarez; Víctor J. García Morales; Aurora Garrido Moreno (The International Journal of Management Science and Information Technology (IJMSIT), 2014)
Nowadays, corporate entrepreneurship is becoming the key source to develop firms in order to improve their results. In this way, technology plays a similar key role so as to obtain higher organizational performance through more efficiently corporate entrepreneurship in the firm. In this regard, the aim of this paper is to introduce how organizational performance on the organization is enhanced by corporate entrepreneurship; which is influenced by technology, through different assets, such as top management support to technology, technological skills, technology acquisition, technological integration and a technological infrastructure.
Keywords: 650; Corporate Entrepreneurship; Organizational Performance; Technological Assets